The Influence of Price, Service Quality and Trust on Consumer Satisfaction at J&T Express Sampang - Sopwan Hadi; Siti Salbiyah; Muhammad Alhakim Danurwindo (P3I UMSurabaya, 2024)
This paper examines the influence of price, quality of service and trust on consumer satisfaction in J&T Express district Sampang. This research method uses a quantitative approach. The data was collected online by distributing questionnaires to 147 respondents. sample technique used with purposive sampling technique. The analytical tool uses SPSS version 25 through the following stages: Validity Test, Reliability Test, Classical Assumption Test, Double Linear Regression Analysis, Determination Coefficient, and Hypothesis Test. The results of this study show that the price has no significant impact on customer satisfaction of J&T Express Waste Branch. The quality of service has a significant positive impact on consumer satisfaction. The trust has significant positive effect on the customer’s satisfaction, and then simultaneously the price, the quality of the service and the trust have an impact on the consumer’s satisfaction.